Adropin and Immune-Reactivity of NUCB2/Nesfatin-1 in Brain Tissue of the Rats with Experimentally Induced Diabetes Mellitus - Ugur, Kader; Kuloglu, Tuncay (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY